Photoconductivity from carbon nanotube transistors activated by photosensitive polymers - Shi, Yumeng (2011)
We perform electrostatic force microscopic measurements to reveal the mechanisms of the photoresponse from polymer-coated carbon nanotube transistors, where the effective gating due to the trapping of photogenerated electrons at SiO2 dielectric surfaces is found dominant. The distant photoresponse and the unique spatial-dependent photoconductivity for polymer-coated SWNT-network transistors are explored for the first time. The photoconductivity depends strongly on the polarity of the applied voltage across the contact pads, which suggests that a secondary effect (electrical field dependent exciton dissociation) needs to be included in addition to the photoinduced electrostatic gating. These spatial photoresponses are generally observed for various substrates and polymers. These results suggest a new strategy for achieving remote light detection, position sensors, or antenna devices.